2022
DOI: 10.1186/s12903-022-02085-6
|View full text |Cite
|
Sign up to set email alerts
|

New technique for detecting cracked teeth and evaluating the crack depth by contrast-enhanced cone beam computed tomography: an in vitro study

Abstract: Background Cracked teeth may cause various clinical symptoms depending on the extension depth of the crack and the subsequent bacterial infections. However, techniques to reliably determine the extension depths of cracks in teeth before treatment are lacking. The aim of this study was to develop a new technique based on contrast-enhanced cone beam computed tomography (CBCT) to improve the accuracy of crack depth evaluation in vitro. Methods We deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The results showed that with the aid of Ioversol, CBCT's ability to identify cracks is significantly improved. This imaging method can only mark the length of crack in the direction of the long axis of the tooth, and the distribution and direction of crack are usually irregular, which reduces the accuracy of the detection results [85] . Yuan M et al [86] used meglumine diatrizoate(MD) as contrast medium to thoroughly soak 24 excised teeth with artificial cracks, and scanned the isolated tooth model with conventional and enhanced CBCT respectively.The results showed that MD enhanced CBCT could significantly improve the identification ability of cracks.…”
Section: Quantitative Evaluation Of Cracked Toothmentioning
confidence: 99%
“…The results showed that with the aid of Ioversol, CBCT's ability to identify cracks is significantly improved. This imaging method can only mark the length of crack in the direction of the long axis of the tooth, and the distribution and direction of crack are usually irregular, which reduces the accuracy of the detection results [85] . Yuan M et al [86] used meglumine diatrizoate(MD) as contrast medium to thoroughly soak 24 excised teeth with artificial cracks, and scanned the isolated tooth model with conventional and enhanced CBCT respectively.The results showed that MD enhanced CBCT could significantly improve the identification ability of cracks.…”
Section: Quantitative Evaluation Of Cracked Toothmentioning
confidence: 99%
“…Several studies have been carried out so far on the depth parameter of cracks 13,15,[20][21][22] . However, the limitations of the techniques used in those studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations of the techniques used in those studies (e.g. the limited penetration depth and scanning range of the device utilized for MCs analysis 15,20 , sensitivity of the technique to surface curvature 13,20 , the depth measurements carried out on a simulated human tooth 13 , an indirect method of determining the depth of the crack 21,22 , the need for crack infiltration with contrast material for depth assessment 22 , or the physical measurement of the crack after cutting the tooth 21 ) have all been the reasons behind the search and development of a new approach enclosing 3D imaging technique that would enable a non-destructive examination of MCs with micrometer resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out so far on the depth parameter of cracks 13 , 15 , 20 22 . However, the limitations of the techniques used in those studies (e.g.…”
mentioning
confidence: 99%
“…However, the limitations of the techniques used in those studies (e.g. the limited depth of penetration and scanning range of the device utilized for MCs analysis 15 , 20 , sensitivity of the technique to surface curvature 13 , 20 , the depth measurements carried out on a simulated human tooth 13 , an indirect method of determining the depth of the crack 21 , 22 , the need for crack infiltration with contrast material for depth assessment 22 , or the physical measurement of the crack after cutting the tooth 21 ) have all been the reasons behind the search and development of a new approach enclosing 3D imaging technique that would enable a non-destructive examination of MCs with micrometer resolution.…”
mentioning
confidence: 99%